Ethics in an epidemic : AIDS, morality, and culture - Murphy, Timothy F., 1955- (University of California Press, 1994)
AIDS strikes most heavily at those already marginalized by conventional society. With no immediate prospect of vaccination or cure, how can liberty, dignity, and reasoned hope be preserved in the shadow of an epidemic? In this humane and graceful book, philosopher Timothy Murphy offers insight into our attempts--popular and academic, American and non-American, scientific and political--to make moral sense of pain. Murphy addresses the complex moral questions raised by AIDS for health-care workers, politicians, policy makers, and even people with AIDS themselves. He ranges widely, analyzing contrasting visions of the origin and the future of the epidemic, the moral and political functions of obituaries, the uncertain value of celebrity involvement in anti-AIDS education, the functional uses of AIDS in the discourse of presidential campaigns, the exclusionary function of HIV testing for immigrants, the priority given to AIDS on the national health agenda, and the hypnotic publicity given to "innocent" victims. Murphy's discussions of the many social and political confusions about AIDS are unified by his attempt to articulate the moral assumptions framing our interpretations of the epidemic. By understanding those assumptions, we will be in a better position to resist self-serving and invidious moralizing, reckless political response, and social censure of the sick and the dying.
Keywords: AIDS (Disease) -- Moral and ethical aspects.; AIDS (Disease) -- Social aspects.; AIDS (Disease) -- Government policy -- United States.; Iatrogenic diseases.; Mortality.; Physicians.; Human experimentation in medicine.; Social change.; Contact tracing (Epidemiology); Medical personnel.; Medical care.; AIDS (Disease); Government aid.; Federal aid.; Drug abuse.; Drug addiction.; Dentistry.; Celebrities.; Politics, Practical.; Homosexuality.; Mass media.; Epidemiology.; International cooperation.; Serodiagnosis.; Vital statistics.; Mental illness.; Sociology.; Research.; HIV infections.; Health planning.; Social sciences.; Diseases.; Therapeutics.; National health services.; Social psychology.; Public health.; Health services accessibility.; Economics.; Slow virus diseases.; Professional ethics.; Immunological deficiency syndromes.; Lentivirus infections.; Virus diseases.; Social control.; Humanities.; Demography.; Immunodiagnosis.; Human behavior.; Science.; Pollution.; Literature.; Literature, Modern.; Philosophy.; Retrovirus infections.; Sexually transmitted diseases.; Immunologic diseases.; Physical sciences.; Diagnosis.; Medical ethics.; Medical policy.; Statistics -- Methodology.; Acquired Immunodeficiency Syndrome -- epidemiology; Iatrogenic Disease; Public Policy; Mortality; Physicians; HIV Seropositivity; Human Experimentation; Social Change; Stereotyping; Contact Tracing; Health Personnel; Mandatory Testing; Patient Care; Vulnerable Populations; Acquired Immunodeficiency Syndrome; Emigration and Immigration; Financing, Government; Health Care Rationing; Morals; Occupational Exposure; Prevalence; Resource Allocation; Substance-Related Disorders; Dentistry; Internationality; Education; Famous Persons; Socioeconomic Factors; AIDS Serodiagnosis; Politics; Homosexuality; Mass Media; Epidemiology; International Cooperation; Biographies as Topic; Serologic Tests; Mandatory Programs; Social Control Policies; Mass Screening